Analisis Peran Bidang PKLK dalam Mendukung Kegiatan Olimpiade Olahraga Siswa Nasional (O2SN) untuk Jenjang SD dan SMP - Rendy Febriyana; Sri Rahayu (CV. Shofanah Media Berkah, 2025)
The development of information technology has encouraged educational institutions to enhance service quality and ensure the effectiveness of programs provided to students. One of these programs is the National Student Sports Olympiad (O2SN) for elementary and junior high school levels. This study aims to analyze the role of the Special Education and Special Services Division (PKLK) of the South Sumatra Provincial Education Office in supporting the implementation of O2SN, including the forms of support, coordination processes, supporting factors, and challenges encountered. This research employs a descriptive qualitative method using interviews, observations, and documentation. The findings indicate that the PKLK Division plays a significant role in activity planning, cross-division coordination, technical facilitation, as well as monitoring and evaluation. However, several challenges remain, such as limited budget allocation, insufficient school understanding of procedures, and suboptimal coordination. These findings are expected to serve as evaluation material for improving the effectiveness of future O2SN implementation and provide practical experience for students in understanding government institutional work processes.